DEVELOPMENT AND EXAMINATION OF SCREENING SYSTEM FOR ORGANIC COMPOUND THAT CAN INHIBIT DIMERIZATION OF CYTOPLASMIC DOMAIN OF PhoR IN Mycobacterium tuberculosis - STEVEN - NIM: 21116029, NATHANAEL
Resistance is the main problem in antibiotic usage as therapy for tuberculosis so therapy approach that can lower resistance is needed. Two-component system PhoRPhoP which controls virulence of Mycobacterium tuberculosis can be targeted for novel tuberculosis drug because compounds that inhibit the system can weaken the virulence of the bacterium so it is easier to be eliminated by immune system. Dimerization of cytoplasmic PhoR (cytoPhoR) is an important step in PhoR-PhoP regulation. Screening of compounds that can inhibit dimerization of cytoPhoR is done by fusing DNA sequence coding cytoPhoR and DNA sequence coding DNA-binding domain of AraC repressor, which from the previous experiment showed to be able to repress the best expression of emerald green fluorescence protein (EmGFP) as reporter gene under the control of araC promoter in pRSET vector. In this research, pRSETaraCsitoPhoR plasmid from previous research was optimized by cytoPhoR coding DNA codon optimization for Escherichia coli BL21(DE3) host and addition of terminator downstream DNA sequence coding fusion protein. Optimized plasmid construct, pAraC_PhoRMTB, was then synthesized and confirmed using DNA sequencing. Confirmed plasmid was then transformed into Escherichia coli BL21(DE3). SDS PAGE analysis of the transformed culture showed a band of 33 kDa size, presumed to be AraC-cytoPhoR fusion protein monomere and reduction of 31 kDa band presumed to be EmGFP, showing that the repression system worked well. Screening of 8 organic compounds, which are chosen based on their antibacterial activity: Panduratin A, JH-1 isolated from black cumin, CMAM, CHAA, CHMM, Luteolin, Apigenin, and Xanthorizol, showed that JH-1 can increase EmGFP fluorescence of the transformed culture the most, up to 36.31% which indicate its ability to inhibit dimerization of cytoPhoR. This result shows that the screening system has been successfully optimized and the compound that can inhibit cytoPhoR dimerization is JH-1.